1998
DOI: 10.1111/j.1467-842x.1998.tb01466.x
|View full text |Cite
|
Sign up to set email alerts
|

The vaccination status of Aboriginal and Torres Strait Island children in Far North Queensland

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(1 reference statement)
0
14
0
Order By: Relevance
“…However, under-identif ication of ASTI individuals in the PDCU and VAED datasets has been demonstrated, 33 indicating that ATSI information from these sources should be viewed with caution. Incomplete immunisation of ATSI children has been found in previous studies of children living in f ar north Queensland 34 and the north coast region of New South Wales. 35 Those in remote areas were more likely to be immunised, 34 compared with those in rural towns or urban settings.…”
Section: Predictors Of Incomplete Immunisationmentioning
confidence: 57%
See 1 more Smart Citation
“…However, under-identif ication of ASTI individuals in the PDCU and VAED datasets has been demonstrated, 33 indicating that ATSI information from these sources should be viewed with caution. Incomplete immunisation of ATSI children has been found in previous studies of children living in f ar north Queensland 34 and the north coast region of New South Wales. 35 Those in remote areas were more likely to be immunised, 34 compared with those in rural towns or urban settings.…”
Section: Predictors Of Incomplete Immunisationmentioning
confidence: 57%
“…Incomplete immunisation of ATSI children has been found in previous studies of children living in f ar north Queensland 34 and the north coast region of New South Wales. 35 Those in remote areas were more likely to be immunised, 34 compared with those in rural towns or urban settings. In a national study, 6 there was poor coverage for DTP of ATSI children at 12 months in both rural and metropolitan areas, while for MMR coverage at 24 months the association was only found in metropolitan areas.…”
Section: Predictors Of Incomplete Immunisationmentioning
confidence: 57%
“…Indigenous children in remote areas of Australia are more readily identif ied and tracked, with immunisation coverage generally better than in metropolitan areas. 22 However, immunisation uptake among Indigenous children in non-remote rural areas may be less. 23 In both rural and metropolitan areas, a high propor tion of single parents was significantly associated with low DTP coverage but not MMR coverage, even after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 99%
“…14 The higher coverage found in this study for Aboriginal and Tor res Strait Islander children living in remote areas is also consistent with other repor ts. 3,4 It is likely that a higher proportion of Aboriginal and Tor res Strait Islander children living in remote areas are more readily identified so are more likely to have been given Pedvax Hib vaccine than the alternate Hibtiter vaccine. Third, the validation analysis of our proxy method of Indigenous assessment indicates that there is considerable consistency between the recording of Indigenous status and the receipt of a Pedvax vaccine recommended only for Indigenous children.…”
Section: Discussionmentioning
confidence: 99%
“…In far north Queensland in 1993/94, 3 only 42% of the Aboriginal and Torres Strait Islander children surveyed were fully vaccinated by their second birthday, with significantly more children in remote communities being fully v accinated than either r ural town or urban children. Similarly, a 1993 study from Western Australia found that vaccination coverage of Aboriginal and Tor res Strait Islander children residing in remote communities w as considerably higher than those from either rural towns or urban areas, 4 as did a 1993 study from the Northern Territor y with the high coverage in remote communities attrib uted to programs managed by Aboriginal health workers.…”
mentioning
confidence: 99%